Optimization of Ultrasonic-Assisted Extraction of Paeoniflorin from Radix Paeoniae Alba - Jin, Jian-Zhong (Asian Journal of Chemistry, 2014)
Ultrasonic-assisted extraction was used to extract paeoniflorin from Radix Paeoniae Alba. Single factor experiment and orthogonal array design were used to study the influences of extracting conditions on the yield of paeoniflorin. The content of paeoniflorin from Radix Paeoniae Alba was determined by UV spectrophotometry. The optimum extracting parameters were established with the liquid to solid ratio of 15 mL/ g, ultrasonic temperature of 50 °C, ultrasonic time of 10 min, ethanol concentration of 40 %. The optimum technology for ultrasonic-assisted extraction of paeoniflorin from Radix Paeoniae Alba is high efficient, extraction yield 8.76 %.